Collegiate Coaches' Knowledge of the Female Athlete Triad in Relation to Their Characteristics - Jillian E. Frideres; Sue G. Mottinger; José M. Palao (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The purpose of this study was to determine what coaches of female athletes know about the female athlete triad. The sample involved 472 NCAA Division I coaches of female athletes. The variables studied were coaches’ knowledge and confidence about the triad and coaches’ characteristics (coach’s gender, age, type of coach, degree held, years of experience in coaching females, continuing education participation specific to the triad and/or triad components, and sport coached). Coaches’ knowledge of the female athlete triad is higher for coaches who have received triad education. No differences regarding knowledge of the female athlete triad were found by gender, degree, experience in coaching female athletes, or coach type. Higher knowledge was found in sports emphasizing low body weight compared to sports that do not emphasize weight. The article discusses the results’ implications and the need for future interventions in this population.